Hubungan Perolehan Nilai Ujian Nasional Fisika Pada Tahun Pelajaran 2011/2012 (Studi Kasus Di SMA Negeri 39 Jakarta Timur) - Alis, Ratih Wulansari (Gema Widyakarya bekerjasama dengan Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
This study aims to determine whether there is a relationship between the acquisition of the value of try out with the value of National Examination physics in the academic year 2011/2012 (case study in SMA Negeri 39 East Jakarta). The hypothesis proposed in this study is